2012
DOI: 10.1007/s00264-012-1513-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative CT with finite element analysis: towards a predictive tool for bone remodelling around an uncemented tapered stem

Abstract: Purpose We used quantitative CT in conjunction with finite element analysis to provide a new tool for assessment of bone quality after total hip arthroplasty in vivo. The hypothesis of this prospective five-year study is that the combination of the two modalities allows 3D patientspecific imaging of cortical and cancellous bone changes and stress shielding. Method We tested quantitative CT in conjunction with finite elements on a cohort of 29 patients (31 hips) who have been scanned postoperatively and at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(36 reference statements)
3
10
0
Order By: Relevance
“…2 DXA-RFA provides a lowradiation dose alternative to computed tomography for such imaging. This approach may provide a novel opportunity to study non-invasively in clinical trials the effect of investigational drugs or implant surface modifications suggested in animal studies to modulate prosthesis osseointegration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 DXA-RFA provides a lowradiation dose alternative to computed tomography for such imaging. This approach may provide a novel opportunity to study non-invasively in clinical trials the effect of investigational drugs or implant surface modifications suggested in animal studies to modulate prosthesis osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…1 This value is calculated as the mean BMD value derived from large numbers of pixels contained within the defined ROI. However, bone remodeling events occurring after prosthesis insertion are spatially complex and may not be uniform across a given ROI, 2 For example, within a large ROI the BMD change occurring over a given time at the bone-prosthesis interface may differ substantially to that occurring at the bone periosteal surface. 2 Such differences cannot be resolved using ROI-based DXA analysis technology, whilst the alternate computed tomography-based approach is accompanied with a higher radiation exposure dose.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We used high order cubic Hermite elements, which preserve both the continuity of nodal values and their first derivatives. This type of element can describe smooth surfaces often found in biological structures such as the heart (Stevens et al, 2003), muscle (Oberhofer et al, 2010) and bone (Munro et al, 2013;Shim et al, 2012) with a lot fewer elements as each node has total 24 degrees of freedom. Therefore, our model has 32 elements and 72 nodes, which corresponds to 1728 degrees of freedom.…”
Section: Generation Of Subject-specific Fe Modelmentioning
confidence: 99%
“…Bone adaptation and remodelling: Bone remodelling simulations have been performed extensively, primarily to assess stress shielding around the femoral component of hip arthroplasty (Perez et al, 2010;Taylor et al, 2004;Weinans et al, 1994;Gupta et al, 2006;Huiskes et al, 1992;Weinans et al, 1992Weinans et al, , 1993Stulpner et al, 1997;Folgado et al, 2009;Pal and Gupta 2011;Shim et al, 2012). Since the publication of the first bone remodelling simulations around implants by Huiskes and co-workers (Huiskes, 1988), there have only been incremental developments, for example accounting for overload induced bone loss (Behrens et al, 2009;Scannell and Prendergast, 2009).…”
Section: Time Dependent/adaptive Modelling Techniquesmentioning
confidence: 99%